The Cultural Competency Scale for Clinical Pediatric Nurse (Ccs-Cpn) in Indonesia: Scale Development and Psychometric Evaluation - Suza, Dewi Elizadiani (Jurnal Keperawatan Soedirman, 2019)
ABSTRACTBackground: Nurses play an important role to apply practice in cultural competence in hospitals. To perform this role nurses need to provide information on the conceptual aspects of cultural competence by using instruments and assessing cultural competence in a clinical setting. Objectives of the study: 1) to develop the cultural competency for clinical pediatric nurse (CCS-CPN), and 2) to psychometric evaluate the validity and reliability of CCS-CPN. Methods: An inductive method was used to develop an instrument to measure nurse perceptions of CCS-CPN. The scale validation was conducted with a purposive sampling of 450 general hospital nurses recruited from twenty general hospitals in Indonesia. DeVellis’ eight-step plan was used to establish guidelines for development the CCS-CPN. The data was examined using exploratory factor analysis (EFA) is a method to identify the internal dimensions of the CCS-CPN. Results: Using an EFA, 30-items with a six-factor structure were retained to form the CCS-CPN. These factors describe: culture awareness of pediatric nurse; culture knowledge of pediatric nurse; culture skill of pediatric nurse; culture encounter of pediatric nurse; culture desire of pediatric nurse; and culture sensitivity of pediatric nurse. The 30-item CCS-CPN yielded an overall Cronbach’s alpha-coefficients .85. The Cronbach’s alpha-coefficients for the CCS-CPN subscales were .81, .73, .81, .75, .78 and .87, respectively. Conclusion: The 30-item CCS-CPN version of Indonesia consists of six-factors were acceptable and significant. Unfortunelly, factor 4 obtained an item that does not represent the dimensions of the culture encounter of pediatric nurses. Therefore, further research is needed by using different method of Delphi method.